Leading Our Frontline HEROES Through Times of Crisis With a Sense of Hope, Efficacy, Resilience, and Optimism - Dimino, Kimberly; Horan, Kathleen M.; Stephenson, Carolene (Nurse leader, 2020)
The coronavirus 2019 (COVID-19) pandemic has changed the trajectory of health care delivery in the United States and the whole world. Frontline nurses—essential warriors in this fight—complete exhausting shifts and experience the moral distress that comes with making difficult ethical decisions. This deeply human crisis requires a deeply human response. To augment the mental health of their frontline staff, nurse leaders must tap into their staff’s psychological capital (PsyCap). PsyCap is characterized by having high levels of HERO (i.e., hope, efficacy, resilience, and optimism). In this article, we describe strategies that nurse leaders can utilize to foster PsyCap in their nurses.